The London Stage 1950-1959: A Calendar of Productions, Performers, and Personnel - Wearing, J. P. (Rowman & Littlefield Publishers, 2014)
Theatre in London has celebrated a rich and influential history, and in 1976 the first volume of J. P. Wearing’s reference series provided researchers with an indispensable resource of these productions. In the decades since the original calendars were produced, several research aids have become available, notably various reference works and the digitization of important newspapers and relevant periodicals. The second edition of The London Stage 1950–1959: A Calendar of Productions, Performers, and Personnel provides a chronological calendar of London shows from the first of January, 1950, through the 31st of December, 1959. The volume chronicles more than 3,100 productions at 52 major central London theatres during this period. For each production the following information is provided: Title Author Theatre Performers Personnel Opening and Closing Dates Number of Performances Other details include genre of the production, number of acts, and a list of reviews. A comment section includes other interesting information, such as plot description, first-night reception by the audience, noteworthy performances, staging elements, and details of performances in New York either prior to or after the London production. Among the plays staged in London during this decade were Look Back in Anger, One Way Pendulum, The Birthday Party, A Taste of Honey, Chicken Soup with Barley, Five Finger Exercise, The Hostage, and Waiting for Godot, as well as numerous musical comedies (British and American), foreign works, operas, ballets, and revivals of English classics. A definitive resource, this edition revises, corrects, and expands the original calendar. In addition, approximately 20 percent of the material—in particular, information of adaptations and translations, plot sources, and comment information—is new. Arranged chronologically, the shows are fully indexed by title, genre, and theatre. A general index includes numerous subject entries on such topics as acting, audiences, censorship, costumes, managers, performers, prompters, staging, and ticket prices. The London Stage 1950-1959 will be of value to scholars, theatrical personnel, librarians, writers, journalists, and historians.